AN OVERVIEW ON THE BIOLOGICAL PERSPECTIVES OF AGLAIA SPECIES - R, Priya; P, Sowmiya; Muthuraman, Meenakshi Sundaram (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Medicinal plants have been identified and used throughout human history for treating various diseases. Plants belonging to genus Aglaia have been used in traditional system of medicine. The genus Aglaia is a member of Meliaceae family. The plants belonging to this genus have various biological activities including antipyretic, astringent, antidiarrheal, antidysenteric, anti-inflammatory, and anticancer activity and are also used in treating skin diseases and tumors. The phytochemistry and the various biological activities of Aglaia sp. such as anticancer, anti-inflammatory, antioxidant, antidiabetic, and nanoparticle activity are discussed in this review paper.